Cardiac Troponin - diagnostic problems and impact on cardiovascular disease. (17th November 2018) - Alaour, Bashir; Liew, Felicity; Kaier, Thomas E.
Abstract: The definition of a high-sensitivity cardiac Troponin (cTn) assay describes the ability to quantify a cardiac biomarker level in at least 50% of healthy individuals. This advance in analytic sensitivity has come with a perceived loss of specificity in the most classic application – chest pain triage and the diagnosis of acute myocardial infarction (AMI). As cardiac Troponin can no longer be used as a dichotomous test, the medical field is increasingly moving towards a more granular interpretation. However, rapid rule-out/rule-in algorithms for AMI still rely on concrete thresholds for efficient triage, irrespective of the patient's comorbidities. Owing to a slightly elevated cTn value, evermore patients appear to fall into an indeterminate risk zone of diagnostic uncertainty. The reasons are manifold, spanning biological variation, analytical issues, increased plasma membrane permeability and the potential cytosolic release of cTn. This review provides a contemporary overview of the literature concerning the use of cardiac Troponin in chronic and acute cardiovascular care. Key messages: High-sensitivity cardiac Troponin assays have transformed the assessment of cardiovascular disease. Rapid rule-out algorithms for chest pain triage have become increasingly complicated, but enable safe rule-out. Cardiac Troponin tracks mid- to long-term risk in patients with hyperlipidaemia, heart failure and renal dysfunction.